RECONSTRUCTIVE SURGERY OF SEVERE DAMAGES OF LOWER EXTREMITIES INTEGUMENT AFTER INJURY - Ponomarenko, O. V. (International Journal of Medicine and Medical Research, 2019)
Background. Injury of lower extremities requires the fastest and most effective method of closing wound surfaces. Objective. The aim of the study was to define the indications and improve the reconstructive interventions for severe damage of lower extremities integument due to mechanical trauma. Methods. During 2008-2016, 242 patients with defects of cover tissues of the body and extremities were operated in the clinic. Depending on the size, depth and degree of tissues damage, all were divided into 4 groups. Results. The lower extremity was the most vulnerable segment (75.2% of patients). Damage Control tactics was used in 83% of cases. To protect the functionally tense areas, free plastics by a split skin graft (the 1st group – 12.8%, the 2nd – 20.4%, the 3rd – 37%, the 4th – 8.9%) were used for closure of the defect. If the wound defect affected functionally significant structures up to 1% of the body surface, the complex flaps of local tissues, tissues close to the defect and anatomically distant areas (the 2nd group – 6%, the 3rd – 10.6%, the 4th – 4.3%) were used. If the defect was more than 1% of the body surface only functionally tense areas were closed with compound complexes of tissues. The rest of the skin was restored by means of autodermoplastics. We suggested and approved our specific protocol of treatment of such injury. Conclusions. Implementation of the suggested protocol of reconstructive interventions for closure of the defects of cover tissues of lower limbs allowed attaining a positive result in 98.8% of the interventions.